A Clinical Review of Statin-Associated Myopathy. (October 2013) - Shannon, Jennifer A.; John, Samuel M.; Parihar, Harish S.; Allen, Shari N.; Ferrara, Jenna J.
Objective: To review the epidemiology, clinical features, proposed mechanisms, risk factors, and management of statin-associated myopathy.Data Sources: Literature searches were conducted in PubMed (1948 to April 2013), TOXLINE, International Pharmaceutical Abstracts (1970 to April 2013), and Google Scholar using the terms statin, hydroxymethylglutaryl-coenzyme A reductase inhibitors, myopathy, myalgia, safety, and rhabdomyolysis. Results were limited to English publications.Study Selection and Data Extraction: All relevant original studies, guidelines, meta-analyses, and reviews of statin-associated myopathy and safety of statins were assessed for inclusion. References from selected articles were reviewed to identify additional citations.Data Synthesis: The 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors remain one of the most effective medications for reducing low-density-lipoprotein cholesterol. Statins are well tolerated by most patients; however, it is estimated that 10% to 15% of patients develop statin-related muscle adverse effects known as statin-associated myopathy. Although clinicians may be aware of statin-associated myopathy, they may not be aware of its clinical presentation. Providers should assess individual patient risk factors before choosing the appropriate statin. A variety of skeletal muscle aches that may not present as a danger to the patient, may affect patient adherence and quality of life. There are several steps that providers can take to properly treat and manage patients with myalgia complaints.Conclusions: Statin-associated myopathy is a clinical problem that contributes to statin therapy discontinuation. Patients who are statin intolerant may be treated with alternative treatment options such as low-dose statins, switching statins, using alternative dosing strategies in statins with longer half-lives, non-statin lipid-lowering agents, and complementary therapies.